INNOVATIVE DEVELOPMENT OF SMALL BUSINESS AS A FACTOR OF SUSTAINABLE DEVELOPMENT OF THE KAZAKHSTAN ECONOMY - Dariskalieva M.S,; Ahmurzina D.О,; Nurzhanova A.Sh,; Abuziarova Zh.R, (Academic Journal of Physical and Chemical Sciences, 2019)
Traditionally, small business is not only a catalyst for economic growth in the economy, but also a guarantor of its stability in solving employment issues, optimizing the industrial sector, the quality of science and innovations, etc. In this connection, the authors of the article consider the innovative development of entrepreneurship as a factor for the sustainable development of the economy of Kazakhstan. The process of innovation development can effectively proceed only in certain conditions created by the innovation environment. Innovation environment is a prerequisite for the formation of an effective innovation system. The development of the country in the future should become innovative, the spatial configuration should become more flexible, not tied to the existing energy source base and centers of concentration of financial flows. Small businesses are most suitable for individual psychological characteristics of a person, they are simpler and more transparent, and therefore accessible to a wide range of citizens.